Law Enforcement of Health Protocols in Controlling The 2019 Corona Virus - Evalina Franciska Hutasoit; Muhammad Ancha Sitorus; Siti Kusyiah Ginting (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
The Coronavirus disease 2019 (COVID-19) is spreading rapidly and has become a worldwide pandemic labeled a public health emergency of international concern. Prevention efforts are carried out, among others, by limiting community activities and implementing health protocols both in public spaces and in the household domain. This study aims to determine the implementation of Deli Serdang Regent's Regulation Number 77 of 2020 concerning discipline and law enforcement of health protocols to control Corona Virus Disease 2019. This study implemented a cross-sectional design by collecting data using a questionnaire and documentation as the secondary data. The number of respondents was 156 people in Sunggal and Hamparan Perak sub-districts, which were taken using a simple random sampling method. The data were analyzed descriptively with George Edwards III's policy implementation approach. Based on the analysis results, it was found that the implementation of Deli Serdang Regent Regulation number 77 of 2020 was carried out in the form of implementing health protocols with a good category by 73.1% of respondents. The health protocol that is most often carried out masks. Factors related to the Deli Serdang Regent's Regulation implementation include policy communication, availability of resource support in the form of cross-sectoral coordination and budgeting, strong cross-sectoral commitment, and a clear bureaucratic structure at each implementation stage of the policies.Abstrak: Corona virus disease 2019 (COVID-19) menyebar dengan cepat dan menjadi pandemi di seluruh dunia dan dilabeli sebagai darurat kesehatan masyarakat yang menjadi perhatian internasional. Upaya pencegahan yang dilakukan antara lain dengan pembatasan aktivitas masyarakat serta pemberlakukan protokol kesehatan di ruang publik maupun dalam skala rumah tangga. Penelitian ini bertujuan untuk mengetahui implementasi Peraturan Bupati Deli Serdang Nomor 77 Tahun 2020 tentang penerapan disiplin dan penegakan hukum protokol kesehatan sebagai upaya pengendalian Corona Virus Disease 2019. Penelitian ini mengimplementasikan desain potong-lintang dengan pengumpulan data menggunakan kuesioner dan dokumentasi data sekunder. Jumlah responden sebesar 156 orang di Kecamatan Sunggal dan Kecamatan Hamparan Perak, yang diambil dengan menggunakan metode simple random sampling. Data dianalisis secara deskritif dengan pendekatan implementasi kebijakan George Edwards III. Berdasarkan Hasil analisis ditemukan bahwa implementasi Peraturan Bupati Deli Serdang nomor 77 tahun 2020 dilaksanakan dalam bentuk pelaksanaan protokol kesehatan dengan kategori baik oleh 73.1% responden. Protokol kesehatan yang paling sering dilakukan adalah penggunaan masker. Faktor – faktor yang berhubungan dengan pengimplementasian Peraturan Bupati ini antara lain komunikasi kebijakan, tersedianya dukungan sumberdaya berupa koordinasi lintas sektor dan sumber dana, komitmen yang kuat dari lintas sektoral, serta struktur birokrasi yang jelas dalam setiap tahapan pelaksanaan kebijakan yang ditetapkan.